Electrochemical formation of titanium-aluminum alloys from Ti2O3 in-situ chloridized by AlCl3 in chloride melts. (10th January 2016) - Yan, Bei-Lei; Yan, Yong-De; Zhang, Mi-Lin; Ye, Yuan-Feng
Abstract: This work presents an electrochemical study of Ti 3+ and Al 3+ in the NaCl-KCl-AlCl3 -Ti2 O3 at 1123K. Transient electrochemical techniques show that Ti 3+ ions are reduced to Ti metal by a two-step mechanism involving the exchanges of one and two electrons. The electrochemical co-reduction of Ti 3+ and Al 3+ in the NaCl-KCl-AlCl3 -Ti2 O3 melts at 1123 K was performed. Cyclic voltammetry and square wave voltammetry were applied using a molybdenum electrode to investigate the reduction behavior of Ti 3+ and Al 3+ and to identify the Ti-Al alloys. A series of redox signals corresponding to different Ti-Al alloys were observed. Potentiostatic electrolysis was conducted using a molybdenum electrode to prepare the Ti-Al alloys. The obtained deposits were characterized by SEM-EDS and XRD. Compounds Layers of TiAl3 and TiAl2 were generated via potentiostatic electrolysis.